Ceramic membrane preparation from waste : effect of binders: article - Zulkefli, Norlydia Azreen; Ibrahim, Norliza (2017)
Porcelain based ceramic supports from sanitary waste were prepared by using different amounts of binders, Polyvinyl Alcohol (PVA) and Polyethylene Glycol (PEG 1500).Converting the sanitary waste into ceramic as a construction material can reduce the utilization cost of the waste but also as an alternative method that has low cost to produce ceramic.The purpose of the research were to identify the ceramic support that has been prepared from the waste and to know the effect of binder on the ceramic support itself. The aimed is to prepare the ceramic membrane support using waste with the help of PVA and PEG as a binders by using compression method. The ceramic properties were analyzed by Fourier Transform Infrared Spectroscopy (FTIR).Result shows that 10wt% PEG is optimum in terms of organic materials as it identify the molecular components and structures exist in the membrane